A Treatise on Efficacy: Between Western and Chinese Thinking - Jullien, Francois (University of Hawaii Press, 2004)
In this highly insightful analysis of Western and Chinese concepts of efficacy, Francois Jullien subtly delves into the metaphysical preconc eptions of the two civilizations to account for diverging patterns of action in warfare, politics, and diplomacy. He shows how Western and C hinese stategies work in several domains (the battle-field, for exampl e) and analyzes two resulting acts of war. The Chinese strategist mani pulates his own troops and the enemy to win a battle without waging wa r and to bring about victory effortlessly. Efficacity in China is thus conceived of in terms of transformation (as opposed to action) and ma nipulation, making it closer to what is understood as efficacy in the West. Jullien's brilliant interpretations of an array of recondite tex ts are key to understanding our own conceptions of action, time, and r eality in this foray into the world of Chinese thought. In its clear a nd penetrating characterization of two contrasting views of reality fr om a heretofore unexplored perspective, Treatise on Efficacy will be o f central importance in the intellectual debate between East and West.